2000
DOI: 10.1046/j.1469-8137.2000.00759.x
|View full text |Cite
|
Sign up to set email alerts
|

Water rise kinetics in refilling xylem after desiccation in a resurrection plant

Abstract: The acropetal water refilling kinetics of the dry xylem of branches (up to 80 cm tall) of the resurrection plant Myrothamnus flabellifolia were determined with high temporal resolution by observation of light refraction at the advancing water front and the associated recurving of the folded leaves. To study the effect of gravity on water rise, data were acquired for cut upright, horizontal and inverted branches. Water rise kinetics were also determined with hydrostatic and osmotic pressure as well as at elevat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
102
1
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(116 citation statements)
references
References 56 publications
11
102
1
2
Order By: Relevance
“…Consistent with the findings of Schneider et al (2000), the NMR measurements showed that the axially advancing water front was not uniform throughout the entire xylem conduit. Figs 1 and 2 show typical sequences of "H-NMR images for acroand basipetal refilling, acquired c. 6 cm from the cut base and apex.…”
Section: Nonuniform Axial and Radial Xylem Refillingsupporting
confidence: 80%
See 4 more Smart Citations
“…Consistent with the findings of Schneider et al (2000), the NMR measurements showed that the axially advancing water front was not uniform throughout the entire xylem conduit. Figs 1 and 2 show typical sequences of "H-NMR images for acroand basipetal refilling, acquired c. 6 cm from the cut base and apex.…”
Section: Nonuniform Axial and Radial Xylem Refillingsupporting
confidence: 80%
“…Because there were no differences in rise time and height between leafy and leafless branches, data were pooled. These parameters were in the range for acropetal water rise measured by the ' light refraction ' and ' leaf recurving ' methods in horizontal branches (Schneider et al, 2000). A few experiments with upright branches (using a vertical 11n7-T NMR magnet) also yielded good agreement with the kinetic data of Schneider et al (2000) ( Table 1).…”
Section: mentioning
confidence: 54%
See 3 more Smart Citations